Avances en el modelamiento y experimentación de tensiones inducidas en redes de distribución (2006)
Abstract. This Phd Thesis was focused on the lightning induced transients modeling on long and complex networks and the induced voltage measurements on energized distribution networks. Here is described and compared two methodologies for the induced transient calculation which are implemented in three different software linked to a transient analysis program (LIOV-EMTP, LIV-ATP and YALUK-ATP). The YALUK-ATP is a software developed in this PhD thesis which improves the link with the transient program; this new proposal allows make link without including an additional delay on the traveling waves. The developed software (YALUK-ATP) and the LIOV-EMTP showed to have the best features calculating lightning-induced voltage on complex networks; these software are used for the analysis of the network topology on lightning-induced voltages calculation for a different stroke location and ground conductivity. Moreover, as an engineering application, it was developed a new software which uses the advantages of YALUKATP and the genetic algorithms technique to locate appropriately surge arresters on a complex distribution network. As a new contribution, it was built a new lightning-induced voltage measurement system on an energized distribution network which uses fiber optics and solar energy technology in order to reduce the electromagnetic interference. This distribution network is located 100m far away from the Colombian direct natural lightning measurement station where the induced voltage signals are gathered and registered. Nowadays, in Colombia, it has been measured more than 200 induced voltages on two measurement systems which were analyzed on this Phd Thesis. Several measurements have been correlated with the Colombian Lightning Location System and compared with calculations made with the induced voltage software.